Task complexity and sources of task-related information during the observational learning process - Laguna, P. L. (Journal of Sports Sciences, 2008)
Although research has examined the influence of various sources of task information for skill acquisition during observational learning, the results have been ambiguous. The purpose of this study was to examine sources of information in relation to the type of task. One hundred and twenty participants were randomly assigned to one of two sets of six treatment strategies: (1) all model demonstrations; (2) model demonstrations with physical practice with knowledge of performance; (3) model demonstrations with physical practice without knowledge of performance; (4) physical practice without knowledge of performance; (5) physical practice with knowledge of performance; or (6) verbal instructions only. One set learned a simple version of the task while the other set learned a more complex version. Cognitive representation and performance accuracy (spatial and temporal) were assessed. Results indicate that task type does influence the source of information to facilitate skill acquisition. The simple task benefited from model demonstrations, physical practice with knowledge of performance, or a combination of model demonstrations and practice both with and without knowledge of performance, while the complex version benefited more from a combination of model demonstrations and knowledge of performance practice. The results of this study provide an insight into the ambiguity that exists within the observational learning and motor learning literature regarding the effectiveness of information sources for motor skill acquisition.